2022
DOI: 10.1002/celc.202200148
|View full text |Cite
|
Sign up to set email alerts
|

From Nickel Foam to Highly Active NiFe‐based Oxygen Evolution Catalysts

Abstract: A key challenge for the large‐scale application of the oxygen evolution reaction (OER) is the synthesis of active, cheap and robust catalysts. Here, a straightforward procedure to form novel porous and highly active multimetallic oxygen evolution catalysts was reported. They were derived from an original dendritic nickel foam (NiNF) using two strategies: i) Fe‐doping; and ii) Fe/Cr‐doping. A bimetallic NiFe catalyst, formed through controlled acid treatment followed by a simple galvanic exchange procedure prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…As shown in Figure 5b the overpotential of 60Fe/NF at 10 mA cm −2 is compared with those of other Ni and Fe‐based catalysts such as Fe‐18 h/NF, [ 4 ] γ‐FeOOH/NF, [ 15 ] NiFe BTC‐GNPs, [ 42 ] NiFe‐LDH, [ 43 ] FeOOH/Ni(OH) 2 /NF, [ 44 ] β‐NiFeOOH/NF, [ 10 ] NiFeMo, [ 45 ] FeNiCr−NiNFc [ 46 ] , and NiFe‐LDH/MXene/NF. [ 47 ] It is found that 60Fe/NF with relatively low overpotential is competitive compared to other Ni─Fe based catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5b the overpotential of 60Fe/NF at 10 mA cm −2 is compared with those of other Ni and Fe‐based catalysts such as Fe‐18 h/NF, [ 4 ] γ‐FeOOH/NF, [ 15 ] NiFe BTC‐GNPs, [ 42 ] NiFe‐LDH, [ 43 ] FeOOH/Ni(OH) 2 /NF, [ 44 ] β‐NiFeOOH/NF, [ 10 ] NiFeMo, [ 45 ] FeNiCr−NiNFc [ 46 ] , and NiFe‐LDH/MXene/NF. [ 47 ] It is found that 60Fe/NF with relatively low overpotential is competitive compared to other Ni─Fe based catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the values of 0.4/0.4/0.2 determined for NiCoCr were consistent with the loss of some Cr(VI) in the form of CrO 4 2− chromate species dissolved in the electrolyte solution, as previously reported by Peugeot et al for NiFeCr electrodes. [ 48 ]…”
Section: Resultsmentioning
confidence: 99%